Religious Moderation in Inter-Ethnic Interaction of Higher Education Students in Aceh - Silahuddin Silahuddin; Fakhrul Rijal; Lismijar Lismijar; Masrizal Masrizal (AL-ISHLAH: Jurnal Pendidikan, 2023)
Higher education in Aceh has students who are diverse in race, ethnicity, culture, and language. Differences often make it difficult to interact and communicate between students, leading to misunderstandings. The research focuses on the discussion of religious moderation in interactions between ethnic students and efforts made to strengthen religious moderation in interactions between ethnicities within the scope of Aceh universities. This study used a qualitative descriptive method and purposive sampling by selecting lecturers and students at tertiary institutions in Aceh as research subjects. Data collection techniques use observation, interviews, and documentation. The results of this study show that student interaction between ethnicities has a positive relationship. This is evidenced by the use of Indonesian for daily interaction so as not to cause misunderstandings. Efforts to build religious moderation to interact with each other between ethnic students are a shared responsibility and duty. Efforts to strengthen religious moderation through religious approaches and humanitarian principles Concrete efforts to strengthen religious moderation through curriculum adjustments related to issues related to religious moderation and the opening of a wide discussion space for students.